KEWENANGAN LEGISLASI DEWAN PERWAKILAN DAERAH TERKAIT RANCANGAN UNDANG-UNDANG DAERAH KEPULAUAN - Watihelu, Abubakar; Mau, Hedwig Adianto; Sagala, Rotua Valentina (CORPUS JURIS : JURNAL ILMU HUKUM, 2026)
This research is motivated by the limited legislative authority of the Regional Representative Council (DPD) in the formulation of the Archipelagic Regions Bill, which is constitutionally participatory rather than decisional in nature. Although the DPD possesses representative legitimacy as a regional chamber and is authorized to propose and deliberate bills related to regional matters, final legislative approval remains vested in the House of Representatives and the President. This condition creates a gap between regional representation and the effectiveness of the DPD in advocating for the interests of archipelagic regions. This study employs the theory of authority and the theory of distributive justice as its theoretical framework. This research adopts a normative legal research method using statutory, conceptual, and analytical approaches. The statutory approach examines constitutional provisions and legislation governing the legislative authority of the DPD. The conceptual approach explores doctrines of authority and the theory of distributive justice, particularly in assessing the allocation of legal benefits and burdens affecting archipelagic regions, while the analytical approach evaluates the consistency between existing legal norms and the practical exercise of the DPD’s legislative authority in the formulation of the Archipelagic Regions Bill. The findings indicate that the legislative authority of the DPD in the formulation of the Archipelagic Regions Bill is normative, procedural, and symbolic, lacking binding decisional power. These limitations have resulted in an uneven realization of distributive justice for archipelagic regions within the national legal framework. This study concludes that an ideal construction of the DPD’s legislative authority requires strengthening its role during deliberative stages, restructuring more effective coordination mechanisms with the House of Representatives, and optimizing its oversight function to ensure that the enactment and implementation of the Archipelagic Regions Law effectively realize distributive justice for archipelagic regions